Towards a Universal Mathematical Braille Notation. (March 2022) - van Leendert, Annemiek; Doorman, Michiel; Drijvers, Paul; Pel, Johan; van der Steen, Johannes
Introduction: Across the world, mathematical expressions are represented very differently in braille. The aim of this study was (1) to gain an overall insight in mathematical braille notations and (2) to investigate how mathematical braille notations support braille readers in reading and comprehending mathematical expressions.Method: Twenty teachers from sixteen countries (thirteen European Union, EU, and three non-EU) were asked to transform 21 mathematical expressions and equations into the mathematical braille notation currently used by their braille readers. Three mathematical expressions were selected, and the transformed expressions in the different braille notations were qualitatively compared at braille and mathematical structure level.Results: The results illustrated that most mathematical braille notations use mathematical structures that either support braille readers in getting an overview of an expression—for example, by announcing the start and end of a fraction—or facilitate communication between braille readers and people who can see.Discussion: The method of comparing transformed expressions at structure level can be extended to other types of mathematical expressions and other mathematical braille notations. Agreement on the structure of different mathematical expressions can be a first step towards a universal mathematical braille notation.Implications for Practitioners: Mathematics teachers should be aware of and use the strengths of the mathematical braille notation and try to compensate for weaknesses of the notation in the support of braille readers.